The relationship between school counselor self-efficacy and burnout among professional school counselors - Manker, Emily E. (Kansas State University, 2022)
The profession of school counseling is seeing an increase in job demands and expectations, such as high student caseloads, role uncertainty, and multiple job responsibilities. With the responsibility increase of the profession, school counselors are at risk for experiencing higher levels of stress, compassion fatigue, vicarious trauma, and burnout. The need for further study was indicated to identify and understand high predictors of school counselor burnout. This quantitative research study examined the relationship between school counselor self-efficacy, measured by the School Counselor Self-Efficacy Scale and burnout, measured by the Maslach Burnout Inventory – Educators Survey. A multivariate regression analysis indicated no significant relationships between the independent variable, school counselor self-efficacy and two subscales of the dependent variables of burnout, emotional exhaustion, and depersonalization. However, there was a significant relationship between school counselor self-efficacy and the third subscale of the dependent variable of burnout, reduced personal accomplishment. The key findings, implications, and recommendations for future research were discussed.
Keywords: School counselor; School counselor self-efficacy; School counselor burnout; Burnout; Self-efficacy